Mechanisms of the JNK/p38 MAPK signaling pathway in drug resistance in ovarian cancer - Ma, Yu-Ting; Li, Chan; Shen, Ying; You, Wan-Hui; Han, Ming-Xuan; Mu, Yi-Fan; Han, Feng-Juan (Frontiers in Oncology, 2025)
Ovarian cancer (OC) is the most lethal malignancy in the female reproductive system, and chemotherapy drug resistance is the main cause of treatment failure. The Mitogen-Activated Protein Kinases (MAPK) pathway plays a pivotal role in regulating cell proliferation, migration, and invasive capacity in response to extracellular stimuli. This review focuses on the mechanisms and therapeutic strategies related to the JNK/p38 MAPK signaling pathway in OC resistance. The JNK/p38 MAPK pathway plays a dual role in OC chemoresistance. This review examines its role in mediating OC treatment resistance by exploring the mechanisms of action of the JNK/p38 MAPK signaling pathway, particularly its involvement in several key biological processes, including apoptosis, autophagy, DNA damage response, the tumor microenvironment (TME), and drug efflux. Additionally, the review investigates the timing of activation of this pathway and its crosstalk with other signaling pathways such as PI3K/AKT and NF-κB. Targeting JNK/p38 MAPK signaling has shown promise in reversing chemoresistance, with several inhibitors and natural compounds demonstrating potential in preclinical studies. Regulating JNK/p38 MAPK may transform what was once a terminal obstacle into a manageable challenge for OC patients with chemotherapy resistance, ultimately improving survival and quality of life.